Kerala’s Differently Abled: A Socio-Economic and Demographic Perspective - Jose, Biji; Muthulakshmi, S. (Innovare Journal of Education, 2025)
The government of India has framed various laws from time to time for the inclusion of differently abled populations into the mainstream of society. The first step in this direction was taken in 1995 with the introduction of the Persons with Disabilities Act. Then, in 2016, the government replaced the Persons with Disabilities Act, 1995, with the Rights of Persons with Disabilities Act, 2016, which aims to protect the rights of the differently abled. The Act provides a comprehensive framework for the inclusion of differently abled individuals in education and employment. Kerala is known for its sound education system, high human development rates, and progressive social and economic policies. The government has taken initiatives to include the marginalized sectors of society, including the differently abled. As a primary step for this initiative, the Government of Kerala conducted a Disability Census under the Social Security Mission in the year 2015 to gain an understanding of the exact number of the differently abled population in the state and to identify their socio-economic position. Any policy formulation for the development of differently abled people requires comprehensive and clear data. Kerala is the only state in India that has conducted an in-depth study about the position of the differently abled population in the state. The present study focuses on the socio-economic and demographic profile of the respondents, based on the Disability Census conducted in 2015 by the Government of Kerala. Through this study, the researcher aims to provide recommendations for the socio-economic development of differently abled persons.